OPTIMASI PEMBUATAN PERNIS DARI DAMAR - Erik Dahlian; Hartoyo Hartoyo; Erra Yusnita (Jurnal Penelitian Hasil Hutan, 2003)
Varnish is a combined  liquid of resin oil, solvent,  pigment,  drying agent, and additives. The additives  in this regard are those  when applied on wood's  surface can form  a dry layer which is harder and firmly stick to the  surface.In a effort  to enhance  damar utilization, an investigation has been conducted on  varnishmanufacturing of damar mata kucing of poor quality type. This investigation was intended to apply appropriate and  more efficient  methods of processing of varnish aimed at improving its quality and increasing  commercial  values aswell.  Meanwhile,  the target  of this investigation was to get  the varnishprocessing methods with low cost of investment which facilitate its application in the damar producing sites more economical.The results of this investigation  revealed that  the processing methods, implemented  by adopting formula  66,0/24,0 k; 65.5/24,5 s and  65,5/24,5 k; were capable of producing varnish with satis factory quality which comply with the requirement of ICI 's paint factory.  The use of low quality damar mata kucing  mixed  with particular  solvent  composed  of toluene   and  kerosene can contribute to the operation of a smallscale industries economically more feasible.